Methyl Jasmonate Regulates Podophyllotoxin Accumulation in Podophyllum hexandrum by Altering the ROS-Responsive Podophyllotoxin Pathway Gene Expression Additionally through the Down Regulation of Few Interfering miRNAs - Hazra, Saptarshi; Bhattacharyya, Dipto; Chattopadhyay, Sharmila (Frontiers in Plant Science, 2017)
Podophylloxin (ptox), primarily obtained from Podophyllum hexandrum, is the precursor for semi-synthetic anticancer drugs viz. etoposide, etopophos and teniposide. Previous studies established that methyl jasmonate (MeJA) treated cell culture of P. hexandrum accumulate ptox significantly. However, the molecular mechanism of MeJA induced ptox accumulation is yet to be explored. Here, we demonstrate that MeJA induces reactive oxygen species (ROS) production, which stimulates ptox accumulation significantly and up regulates three ROS-responsive ptox biosynthetic genes, namely, PhCAD3, PhCAD4 (cinnamyl alcohol dehydrogenase) and NAC3 by increasing their mRNA stability. Classic uncoupler of oxidative phosphorylation, carbonylcyanide m-chlorophenylhydrazone (CCCP), as well as H2O2 treatment induced the ROS generation and consequently, enhanced the ptox production. However, when the ROS was inhibited with NADPH oxidase inhibitor diphenylene iodonium (DPI) & Superoxide dismutase inhibitor diethyldithio-carbamic acid (DETC), the ROS inhibiting agent, the ptox production was decreased significantly. We also noted that, MeJA up regulated other ptox biosynthetic pathway genes which are not affected by the MeJA induced ROS. Further, these ROS non-responsive genes were controlled by MeJA through the down regulation of five secondary metabolites biosynthesis specific miRNAs viz. miR172i, miR035, miR1438, miR2275 and miR8291. Finally, this study suggested two possible mechanisms through which MeJA modulates the ptox biosynthesis: primarily by increasing the mRNA stability of ROS-responsive genes and secondly, by the up regulation of ROS non-responsive genes through the down regulation of some ROS non-responsive miRNAs.